In Silico Assessment of Efficacy and Safety of IKur Inhibitors in Chronic Atrial Fibrillation: Role of Kinetics and State-Dependence of Drug Binding - Ellinwood, Nicholas; Dobrev, Dobromir; Morotti, Stefano; Grandi, Eleonora (Frontiers in Pharmacology, 2017)
Current pharmacological therapy against atrial fibrillation (AF), the most common cardiac arrhythmia, is limited by moderate efficacy and adverse side effects including ventricular proarrhythmia and organ toxicity. One way to circumvent the former is to target ion channels that are predominantly expressed in atria vs. ventricles, such as KV1.5, carrying the ultra-rapid delayed-rectifier K+ current (IKur). Recently, we used an in silico strategy to define optimal KV1.5-targeting drug characteristics, including kinetics and state-dependent binding, that maximize AF-selectivity in human atrial cardiomyocytes in normal sinus rhythm (nSR). However, because of evidence for IKur being strongly diminished in long-standing persistent (chronic) AF (cAF), the therapeutic potential of drugs targeting IKur may be limited in cAF patients. Here, we sought to simulate the efficacy (and safety) of IKur inhibitors in cAF conditions. To this end, we utilized sensitivity analysis of our human atrial cardiomyocyte model to assess the importance of IKur for atrial cardiomyocyte electrophysiological properties, simulated hundreds of theoretical drugs to reveal those exhibiting anti-AF selectivity, and compared the results obtained in cAF with those in nSR. We found that despite being downregulated, IKur contributes more prominently to action potential (AP) and effective refractory period (ERP) duration in cAF vs. nSR, with ideal drugs improving atrial electrophysiology (e.g., ERP prolongation) more in cAF than in nSR. Notably, the trajectory of the AP during cAF is such that more IKur is available during the more depolarized plateau potential. Furthermore, IKur block in cAF has less cardiotoxic effects (e.g., AP duration not exceeding nSR values) and can increase Ca2+ transient amplitude thereby enhancing atrial contractility. We propose that in silico strategies such as that presented here should be combined with in vitro and in vivo assays to validate model predictions and facilitate the ongoing search for novel agents against AF.